The sociocybernetics of observation and reflexivity. (July 2019) - Scott, Bernard
The aim of this article is to show how sociocybernetics can clarify and bring order to two key concepts in the social sciences: 'observation' and 'reflexivity'. The article provides an introduction and conceptual overview of second order cybernetics, placing it in the larger context of cybernetics and systems sciences studies. Since its inception, in cybernetics the role of the observer has been paramount. It is the observer who distinguishes systems of interest. It is the observer who communicates her observations and theoretical interpretations to the wider community of other observers. Critically, as Heinz von Foerster emphasises, with second order cybernetics the observer, since she is herself an observing system, should 'enter the domain of her own descriptions'. With her second order studies, she is explaining herself to herself. Reflexively, she is obliged to engage in self-observation. The article sets out some of the theoretical and methodological implications of these propositions.